Design of First Generation of Sunan Kalijaga’s High Power UV-LED Fluoerescence Spectroscopy System - Rakhmadi, Frida Agung; Rifai, Rochan; Khamidinal (Proceeding International Conference on Science and Engineering, 2020)
Research on design of the first generation of Sunan Kalijaga’s high power UV-LED fluorescence spectroscopy system has been done. The purpose of this research was to make the first generation of Sunan Kalijaga’s high power UV-LED fluorescence spectroscopy system. This research was done in two steps, designing and manufacturing of the system. The result showed that a fluorescence spectroscopy system has been made succesfully using high power UV-LED of waveleght 365 nm as excitation source and webcam M-Tech WB100 as sensor. The data acquisition software was successfully created using LabVIEW.